Disease-relevant transcriptional signatures identified in individual smooth muscle cells from healthy mouse vessels - Lina Dobnikar (Nature Portfolio, 2018)
Vascular smooth muscle cell (VSMC) accumulation is associated with cardiovascular disease. Here, the authors combine single-cell RNA sequencing with lineage labelling to profile VSMC heterogeneity in healthy mice. They show that upregulation of Sca1 in a rare VSMC subpopulation marks a cell phenotype that is prevalent in disease.